Immune system modelling and simulation - Castiglione, Filippo, 1969-; Celada, Franco (CRC Press, 2015)
Immunology for aliensLeo Szilard paradox: Grand Central TerminalNon-specific defenseLevels of evolution How is a trait selected if it was not needed?Luck or foresight?Blood brothers The members of the winning team are rewarded Somatic recombination produces diversity among equals The workshop of the adaptive response Repertoires A battalion of one Self-inflicted damage threatens survival Don't think, but reason and understandFull cover comes at a cost A bet, not a fantasy, about earliest happeningsThe cooperation of very different cells multiplies jobs that can be done Thymus deeds Hypothesis.